2023
DOI: 10.1017/s1049023x23006179
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Preparedness and Hospital Safety in State Hospitals in Lima (Peru)

Abstract: Introduction: Peru’s health infrastructures, particularly hospitals, are exposed to disaster threats of different natures. Traditionally, earthquakes have been the main disaster in terms of physical and structural vulnerability, but the coronavirus disease 2019 (COVID-19) pandemic has also shown their functional vulnerability. Public hospitals in Lima are very different in terms of year constructed, type of construction, and number of floors, making them highly vulnerable to earthquakes. In addition, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…It is important to highlight that there is a discrepancy in reporting the directionality of the relationship between length of work experience and psycho-emotional impact. While in Turkey (22) and Peru (8) they found that there is a direct relationship, in the United States they indicate that there is an inverse correlation (23) . Therefore, it is necessary to continue carrying out other studies to clarify this relationship.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It is important to highlight that there is a discrepancy in reporting the directionality of the relationship between length of work experience and psycho-emotional impact. While in Turkey (22) and Peru (8) they found that there is a direct relationship, in the United States they indicate that there is an inverse correlation (23) . Therefore, it is necessary to continue carrying out other studies to clarify this relationship.…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, in The COVID-19 Health Care Workers Study (HEROES), carried out in 2020 in 26 countries, it was highlighted that approximately a quarter of health professionals manifested depressive symptoms, that is, about 15% considered committing suicide (7) . In Peru, 39.1% of nurses had anxiety, while 24.6% had depression and only 8.8% had stress (8) .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…There has been a reported prevalence of depression and anxiety of 16.2% and 27.3% among teachers, 19.6% and 17.3% in police officers, and 24.6% and 39.1% in healthcare workers, respectively, during the pandemic. Therefore, the sequels in these vulnerable occupational groups might represent a higher burden of professional illnesses in its economic sector [13,14,16].…”
Section: Evaluation Of Usability and Acceptability Of Telemental Heal...mentioning
confidence: 99%
“…5 La pandemia por COVID-19 no solo repercute en la salud física, también ha ocasionado el incremento de problemas de salud mental, especialmente en los profesionales de enfermería que se han visto expuestos a situaciones laborales muy complicadas sumadas al abarrotamiento de ansiedad y estrés vividos en los servicios de emergencia. 6 El estrés que enfrentan los profesionales de enfermería durante la pandemia no solo proviene de la carga de trabajo y las condiciones laborales difíciles, sino también de la preocupación constante por su propia salud y la de sus seres queridos. Esta tensión adicional puede tener un impacto significativo en la percepción y toma de decisiones de los enfermeros, ya que el agotamiento físico y emocional puede afectar su capacidad para evaluar de manera objetiva y precisa la situación clínica.…”
Section: Introductionunclassified